Strangers in a strange land : living the Catholic faith in a post-Christian world - Chaput, Charles J. (Henry Holt and Company, 2017)
The archbishop of Philadelphia presents a hopeful treatise for Catholics on how to live the faith with confidence in today's post-Christian culture while evaluating the reasons behind declining Catholic numbers.